Conductive glass and preparation method thereof

Through the collaborative design of graphene and indium tin oxide, an efficient conductive network is built, which solves the problem of difficult balance between conductivity and transparency of conductive glass, and realizes high-performance conductive glass, suitable for a variety of optoelectronic devices.

CN119954403APending Publication Date: 2025-05-09SHENZHEN JUNTONG ELECTRONIC TECH CO LTD

Patent Information

Application Number
CN202510198161.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-22
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

The existing conductive glasses are difficult to balance between conductivity and transparency, and their applications in the fields of flexible electronics and high-efficiency photovoltaic devices are limited by mechanical stability, environmental adaptability and cost.

Method used

The coordinated design of graphene and indium tin oxide is adopted. Graphene is distributed in a three-dimensional network structure, and indium tin oxide exists in the form of nanorods. By reasonably controlling the volume ratio and structural size, an efficient conductive network is built.

Benefits of technology

The high conductivity and high light transmittance of conductive glass are achieved, mechanical stability is enhanced, suitable for touch panels, photovoltaic devices and flexible electronics, and cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119954403A_ABST
    Figure CN119954403A_ABST
Patent Text Reader

Abstract

The invention relates to the field of conductive glass, and provides conductive glass and a preparation method thereof.The conductive glass is composed of graphene and indium tin oxide, the graphene is of a three-dimensional connected net structure, and the indium tin oxide contains crystalline nanorods. The preparation method comprises the following steps: (1) taking Au as a catalyst, and preparing an indium tin oxide nanorod through high-temperature reaction of indium oxide, tin oxide and activated carbon; (2) preparing graphene by combining an improved Hummers method with a chemical reduction method; (3) preparing composite sol through a sol-gel method of indium chloride and tin chloride and ultrasonic dispersion of the indium tin oxide nanorods and graphene; and (4) coating a corundum substrate with the composite sol, drying, and carrying out high-temperature annealing in a nitrogen-hydrogen atmosphere to obtain the conductive glass. The obtained conductive glass has excellent conductivity and transparency, and is suitable for the fields of photoelectric devices and transparent electrodes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of conductive glass, and in particular to conductive glass and a preparation method thereof. Background Art

[0002] In the rapid development of modern optoelectronic devices, smart displays and new energy industries, high-performance conductive glass has become one of the indispensable core materials and is widely used in touch screens, transparent electrodes, photovoltaic cells, electrochromic devices and other fields. In these application scenarios, conductive glass not only needs to have good conductivity to ensure the efficiency of electron transmission, but also must maintain high transparency to ensure optical performance, so as to meet the requirements of photoelectric conversion, display clarity and energy utilization. Especially in the field of flexible electronics and high-efficiency photovoltaic devices, the performance of conductive glass directly determines the overall efficiency and durability of the equipment. Therefore, how to strike a balance between high conductivity and high transmittance has become a key challenge for research and application in this field. In addition, as new electronic devices develop towards lightweight, flexible and efficient directions, conductive glass also needs to have good mechanical stability, environmental adaptability and low square resistance to ensure that it can maintain stable electrical and optical properties under complex working conditions. Therefore, further improving the comprehensive performance of conductive glass will not only help to improve the application level of existing optoelectronic technologies, but also promote the development of a new generation of high-performance transparent electronic devices, providing important material support for intelligent manufacturing, wearable devices and new energy industries.

[0003] At present, the conductive glass on the market mainly adopts doped indium tin oxide film or other transparent conductive oxide materials, but these materials still have contradictions between conductivity and transparency. For example, the publication number CN117865505A discloses a method for preparing ITO conductive glass and ITO conductive glass, which uses magnetron sputtering technology to deposit ITO film and uses heat treatment to improve crystallinity. Although transparent conductivity can be achieved to a certain extent, due to the inherent limitations of ITO, the square resistance of the film is still high, and it is difficult to meet the demand for higher conductivity. At the same time, the conductivity of ITO material is improved when the film layer is thicker, but the transparency will be significantly reduced. In addition, due to the limited indium resources, ITO has a high cost and is easy to crack under bending and high temperature conditions, which limits its application in flexible electronic devices. Therefore, there is still room for optimization in the existing conductive glass technology in terms of conductivity and transparency, especially for new conductive glass materials with high performance, low cost, and large-scale preparation, it is still necessary to explore better material systems and preparation processes to simultaneously improve its conductivity and transparency, so as to meet the needs of future optoelectronic device development. Summary of the invention

[0004] (1) Technical issues solved

[0005] The purpose of the present invention is to provide a conductive glass and a preparation method thereof, so as to solve the problem that the current conductive glass has insufficient conductivity and transparency.

[0006] (2) Technical solution

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] A conductive glass, wherein the conductive glass is composed of graphene and indium tin oxide;

[0009] The volume ratio of graphene to indium tin oxide is (1.0-5.0): (99.0-95.0);

[0010] The graphene presents a three-dimensional interconnected network structure in the conductive glass;

[0011] The indium tin oxide contains crystalline indium tin oxide nanorods;

[0012] The indium tin oxide nanorods account for 5.0% to 15.0% of the volume fraction of the conductive glass;

[0013] The average length of the indium tin oxide nanorods is 200-1000nm; the average diameter is 10-45nm.

[0014] Furthermore, the thickness of the graphene is 1.0 to 2.5 nm.

[0015] Furthermore, the conductive glass has a block resistance of 20 to 50 Ω / sq, and a light transmittance of 80 to 85% within a wavelength range of 400 to 800 nm.

[0016] The present invention adopts the collaborative design of graphene and indium tin oxide, which is mainly used to enhance the conductivity and optical transparency of conductive glass. Graphene is distributed in the conductive glass in a three-dimensional interconnected mesh structure, forming an efficient electron transmission network with indium tin oxide. Graphene has excellent conductivity and high electron mobility, and its unique two-dimensional structure helps to build a continuous conductive path inside the conductive glass, thereby reducing the overall resistance and improving the carrier transmission efficiency. At the same time, indium tin oxide exists in the form of nanorods, and its crystalline structure provides additional electron channels and further optimizes the conductive properties of the film. The volume ratio of graphene to indium tin oxide is controlled within a reasonable range to ensure that the two achieve the best balance between conductivity and transparency. The size of indium tin oxide nanorods is precisely controlled so that while enhancing the conductive properties, it avoids scattering losses caused by excessive size, thereby maintaining high light transmittance. In addition, the thickness of graphene is controlled at 1.0 to 2.5 nm to ensure that its number of layers is moderate to avoid enhanced light absorption caused by excessive stacking, while ensuring the effectiveness of its conductive network. In general, the present invention achieves excellent conductivity and optical transparency of conductive glass by optimizing the structure and ratio of graphene and indium tin oxide, providing a reliable material basis for high-performance optoelectronic devices.

[0017] The present invention also provides a method for preparing conductive glass, comprising the following steps:

[0018] S1. Preparation of indium tin oxide nanorods: Using Au as a catalyst, indium tin oxide, tin oxide and activated carbon are reacted at high temperature under argon gas flow to prepare indium tin oxide nanorods on a silicon substrate;

[0019] S2. Preparation of graphene: Graphene is prepared by a modified Hummers method combined with a chemical reduction method;

[0020] S3. Preparation of composite sol: preparing an initial sol by reflux reaction of indium chloride and tin chloride in acetylacetone and ethanol system, and introducing graphene and indium tin oxide nanorods to prepare a composite sol by ultrasonic dispersion method;

[0021] S4. Preparation of conductive glass: The composite sol is coated on a soda-lime glass substrate, dried and annealed at a high temperature to obtain the conductive glass.

[0022] Further, the detailed preparation process of step S1 is as follows: 5 to 15 parts of indium oxide, 1.0 to 3.0 parts of tin oxide and 0.5 to 2.0 parts of activated carbon are mixed uniformly by weight and loaded into an alumina boat, the alumina boat containing the mixture is placed in the center of the first heating zone of a three-zone tube furnace, and at the same time, a 3.0 to 10.0 nm Au layer is prepared on the silicon substrate cleaned by sonication by magnetron sputtering, and then placed in the third heating zone, and then argon is used as a carrier gas with a flow rate set to 80 ~120sccm, during the reaction process, the temperature of the first heating zone is increased to 850~950℃ at a heating rate of 5~10℃ / min, and kept warm for 50~70min, and the temperature of the third heating zone is heated to 850~880℃ at the same heating rate, and the reaction is kept at a constant temperature. After the reaction is carried out for 60~90min, the furnace is cooled to room temperature, and then the crude indium tin oxide nanorods on the silicon substrate in the alumina boat in the third heating zone are collected, and then the indium tin oxide nanorods are obtained after grinding and screening.

[0023] Further, the detailed preparation process of step S2 is as follows: by weight, 1.0 to 3.0 parts of natural graphite are added to a stirring bottle, followed by adding 12 to 35 parts of 98 wt.% concentrated sulfuric acid, stirring for 3 to 10 minutes at 0 to 5 ° C in an ice bath to form a uniform dispersion system, then slowly adding 3.0 to 5.0 parts of potassium permanganate, maintaining a stirring rate of 200 to 500 rpm, stirring for 90 to 240 minutes at 45 to 50 ° C to form an oxidized graphite intermediate, then transferring the obtained oxidized graphite intermediate to a 95 to 100 ° C glycerol bath, slowly adding 20 to 50 parts of deionized water, and maintaining stirring for 10 to 20 minutes, then slowly adding 2.5 to 5.0 parts of 30 wt.% hydrogen peroxide solution to terminate the oxidation reaction to obtain an oxidized graphite suspension, and the obtained oxidized graphite suspension is subjected to solid-liquid separation by vacuum filtration through a Buchner funnel, retaining the filter cake, and the filter cake is successively treated with 0.1 to 0.5 mol / L hydrochloric acid and The mixture was washed with deionized water for 3 times in sequence, with the volume of each washing liquid being 3 to 6 times the volume of the precipitate. The washed graphite oxide dispersion was centrifuged at a centrifugal rate of 4000 to 8000 rpm for 10 to 30 min, the supernatant was discarded, and the precipitate was collected. Finally, the obtained graphene oxide dispersion system was dried under vacuum drying at 60 to 90 ° C for 24 to 48 h to obtain graphene oxide powder. The graphene oxide powder was then redispersed in 50 to 100 mL of deionized water, stirred evenly, 5 to 10 parts of 25 wt.% tetramethylammonium hydroxide were added, and then 0.8 to 4.5 parts of L-ascorbic acid were added dropwise, stirred at 50 to 80 ° C for 30 to 120 min, and the reaction was stopped after the color changed from yellow brown to black. The obtained reduced graphene oxide was centrifuged at a centrifugal rate of 6000 to 10000 rpm for 20 to 40 min, then washed with deionized water for 3 to 5 times, and finally dried in vacuum for 24 to 48 h to obtain graphene powder.

[0024] Further, the detailed preparation process of step S3 is as follows: by weight, 8.0 to 12.0 parts of indium chloride and 12.0 to 25.0 parts of acetylacetone are mixed, the mixed raw materials are placed in a three-necked flask, stirred at a stirring rate of 300 to 500 rpm, stirred for 30 to 60 minutes to obtain a uniform mixed solution, then, the resulting solution is transferred to a reflux device, and continued to stir at a stirring rate of 400 to 600 rpm for 60 to 90 minutes to obtain a uniform indium chloride complex solution, and the complex solution is heated at a heating rate of 2 to 5 ° C / m in is heated to 85-90°C and kept warm for 60-90 minutes. Stirring is continued during the heat preservation period. After the heat preservation is completed, 0.5-1.2 parts of graphene, 3.0-8.0 indium tin oxide nanorods and 0.2-0.5 parts of polyvinyl pyrrolidone are added, followed by ultrasonic treatment at 80-100kHz for 30-45 minutes. Then, 3.0-7.0 parts of 0.02-0.06 mol / L tin chloride ethanol solution are slowly added, and constant temperature stirring is maintained for 60-90 minutes. After the reaction is completed, the sol is naturally cooled to room temperature to obtain a composite sol.

[0025] Furthermore, the detailed preparation process of step S4 is: coating the composite sol on a corundum substrate and drying it at 350-400° C. to constant weight, and finally annealing at 500-550° C. in a mixed atmosphere of nitrogen and hydrogen, wherein the volume ratio of nitrogen to hydrogen is 95:5, for 60-120 min, and obtaining a conductive glass after cooling to room temperature.

[0026] The present invention adopts the design of indium tin oxide nanorods and graphene to collaboratively construct a composite conductive network, which is mainly used to enhance the conductivity and optical transparency of conductive glass. Indium tin oxide nanorods generated by high temperature reaction under argon carrier flow, with indium oxide, tin oxide and activated carbon as precursors, and Au as a catalyst, have good crystalline structure and excellent electron transmission ability, forming a highly ordered conductive path in the conductive glass, thereby effectively reducing the sheet resistance. At the same time, the graphene prepared by the improved Hummers method combined with the chemical reduction method is well dispersed in the composite sol system by virtue of its high conductivity and two-dimensional layered structure, and a three-dimensional interconnected mesh structure is constructed in the conductive glass, which cooperates with the indium tin oxide nanorods to further optimize the electron transmission efficiency. A uniform initial sol is obtained by the reflux reaction of indium chloride and tin chloride in acetylacetone and ethanol system, and combined with ultrasonic dispersion technology, graphene and indium tin oxide nanorods are evenly distributed in the composite sol, thereby ensuring the continuity and stability of the conductive network. Finally, the composite sol is evenly coated on the corundum substrate and annealed at high temperature in a mixed atmosphere of nitrogen and hydrogen to further densify the composite structure, improve the conductivity and light transmittance of the material, and ensure the stability and uniformity of the film. Overall, the present invention achieves excellent conductivity and optical transparency of conductive glass by rationally designing the size and content of indium tin oxide nanorods, optimizing the thickness and distribution of graphene, and using an efficient sol-gel method and annealing process, providing key functional materials for high-performance optoelectronic devices.

[0027] (3) Beneficial technical effects

[0028] 1. The present invention achieves a balance between high conductivity and high transmittance of conductive glass through the coordinated design of graphene and indium tin oxide. Compared with traditional ITO films, it reduces resistance and improves optical performance, while enhancing mechanical stability, and is suitable for touch panels, photovoltaic devices and flexible electronics. Graphene constructs a three-dimensional conductive network to improve electron mobility, and indium tin oxide nanorods provide stable electron channels. The two work together to optimize interface bonding and carrier transport. The component ratio and size are precisely controlled, and the sol-gel method and annealing process are combined to ensure network uniformity and density. The overall performance is better than the existing technology, promoting the development of optoelectronic materials.

[0029] 2. The present invention realizes a highly ordered conductive network through the coordinated construction of indium tin oxide nanorods and graphene, significantly reducing the square resistance and improving the optical transparency. Indium tin oxide nanorods are synthesized by Au-catalyzed high-temperature reaction to ensure that their crystalline structure optimizes the electron transmission performance. Combined with the highly conductive graphene prepared by the improved Hummers method, a three-dimensional interconnected network is constructed to further improve the carrier transmission efficiency. The sol-gel method and ultrasonic dispersion technology are used to achieve uniform distribution of components, and the film density and stability are enhanced by high-temperature annealing, which improves the performance of conductive glass as a whole and provides efficient and stable functional materials for optoelectronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a morphology of graphene after etching indium tin oxide on the conductive glass prepared in Example 1 of the present invention.

[0031] Figure 2 This is a morphology picture of the indium tin oxide nanorods prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0032] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0033] Example 1

[0034] A conductive glass, the conductive glass is composed of graphene and indium tin oxide; the volume ratio of graphene to indium tin oxide is 1.0:99.0; the graphene presents a three-dimensional interconnected network structure in the conductive glass; the indium tin oxide contains crystalline indium tin oxide nanorods; the indium tin oxide nanorods account for 5.0% of the volume fraction of the conductive glass; the average length of the indium tin oxide nanorods is 200nm; the average diameter is 10nm. The thickness of the graphene is 1.0nm. The square resistance of the conductive glass is 50Ω / sq; and the light transmittance in the wavelength range of 400 to 800nm ​​is 85%.

[0035] A method for preparing a conductive glass according to the present embodiment comprises the following steps:

[0036] S1. Preparation of indium tin oxide nanorods: Using Au as a catalyst, indium tin oxide, tin oxide and activated carbon are reacted at high temperature under argon gas flow to prepare indium tin oxide nanorods on a silicon substrate; the detailed preparation process is as follows: 5 parts of indium oxide, 1.0 part of tin oxide and 0.5 part of activated carbon are mixed evenly by weight and loaded into an alumina boat, the alumina boat containing the mixture is placed in the center of the first heating zone of a three-temperature zone tube furnace, and a 3.0 nm Au layer is prepared on the silicon substrate cleaned by sonication by magnetron sputtering. It is then placed in the third heating zone, and argon is used as the carrier gas with a flow rate set to 80 sccm. During the reaction, the temperature of the first heating zone is increased to 850°C at a heating rate of 5°C / min and kept warm for 50 minutes. At the same time, the temperature of the third heating zone is heated to 850°C at the same heating rate and a constant temperature reaction is maintained. After 60 minutes of reaction, the furnace is cooled to room temperature, and then the crude indium tin oxide nanorods on the silicon substrate in the alumina boat in the third heating zone are collected, and then ground and screened to obtain the indium tin oxide nanorods.

[0037] S2. Preparation of graphene: Graphene is prepared by a modified Hummers method combined with a chemical reduction method; the detailed preparation process is as follows: by weight, 1.0 part of natural graphite is added to a stirring bottle, followed by adding 12 parts of 98wt.% concentrated sulfuric acid, stirring for 3 minutes in an ice bath at 0°C to form a uniform dispersion system, then slowly adding 3.0 parts of potassium permanganate, maintaining a stirring rate of 200rpm, stirring for 90 minutes at 45°C to form an oxidized graphite intermediate, then transferring the obtained oxidized graphite intermediate to a 95°C glycerol bath, slowly adding 20 parts of deionized water, and maintaining stirring for 10 minutes, then slowly dropping 2.5 parts of 30wt.% hydrogen peroxide solution to terminate the oxidation reaction to obtain an oxidized graphite suspension, and the obtained oxidized graphite suspension is subjected to solid-liquid separation by vacuum filtration through a Buchner funnel, retaining the filter cake, The filter cake was washed three times with 0.1 mol / L hydrochloric acid and deionized water in sequence, and the volume of each washing liquid was 3 times the volume of the precipitate. The washed graphite oxide dispersion was centrifuged at a centrifugal rate of 4000 rpm for 10 min, the supernatant was discarded, and the precipitate was collected. Finally, the obtained graphene oxide dispersion was dried at 60 ° C under vacuum for 24 h to obtain graphene oxide powder. Then, the graphene oxide powder was redispersed in 50 mL of deionized water, stirred evenly, 5 parts of 25 wt.% tetramethylammonium hydroxide were added, and then 0.8 parts of L-ascorbic acid were added dropwise, stirred at 50 ° C for 30 min, and the reaction was stopped after the color changed from yellow brown to black. The obtained reduced graphene oxide was centrifuged at a centrifugal rate of 6000 rpm for 20 min, then washed three times with deionized water, and finally dried in vacuum for 24 h to obtain graphene powder.

[0038] S3. Preparation of composite sol: an initial sol is prepared by reflux reaction of indium chloride and tin chloride in acetylacetone and ethanol system, and graphene and indium tin oxide nanorods are introduced by ultrasonic dispersion method to prepare composite sol; the detailed preparation process is as follows: 8.0 parts of indium chloride and 12.0 parts of acetylacetone are mixed by weight, the mixed raw materials are placed in a three-necked flask, stirred at a stirring rate of 300 rpm for 30 minutes to obtain a uniform mixed solution, and then the resulting solution is transferred to a reflux device and continued to be stirred at a stirring rate of 400 rpm. The mixture was stirred for 60 min to obtain a uniform indium chloride complex solution, and the complex solution was heated to 85 °C at a heating rate of 2 °C / min and kept warm for 60 min. Stirring was continued during the insulation period. After the insulation was completed, 0.5 parts of graphene, 3.0 indium tin oxide nanorods and 0.2 parts of polyvinyl pyrrolidone were added, followed by ultrasonic treatment at 80 kHz for 30 min, and then 3.0 parts of 0.02 mol / L tin chloride ethanol solution were slowly added, and constant temperature stirring was maintained for 60 min. After the reaction was completed, the sol was naturally cooled to room temperature to obtain a composite sol.

[0039] S4. Preparation of conductive glass: The composite sol is coated on a soda-lime glass substrate, dried and annealed at high temperature to obtain conductive glass. The detailed preparation process is: the composite sol is coated on a corundum substrate and dried at 350°C to constant weight, and finally annealed at 500°C in a mixed atmosphere of nitrogen and hydrogen, wherein the volume ratio of nitrogen to hydrogen is 95:5 for 60 minutes, and the conductive glass is obtained after cooling to room temperature.

[0040] Depend on Figure 1 It can be seen that after etching indium tin oxide, the graphene in the conductive glass prepared in Example 1 of the present invention presents a three-dimensional interconnected network structure, which helps to form a stable and efficient electron transmission channel and improve the conductive performance and stability of the conductive glass. Figure 2 The morphology of the indium tin oxide nanorods in Example 1 of the present invention is shown, confirming that it has a distinct rod-like structure. This one-dimensional nanostructure can provide a good electron transmission path in the conductive glass, and synergize with the three-dimensional graphene network to further optimize the uniformity and connectivity of the conductive network, thereby improving the overall conductive performance and optical transparency. The above results fully prove that the present invention achieves high-performance conductive glass by rationally designing the structure of graphene and indium tin oxide nanorods.

[0041] Example 2

[0042] A conductive glass, the conductive glass is composed of graphene and indium tin oxide; the volume ratio of graphene to indium tin oxide is 2.2:97.8; the graphene presents a three-dimensional interconnected network structure in the conductive glass; the indium tin oxide contains crystalline indium tin oxide nanorods; the indium tin oxide nanorods account for 8.0% of the volume fraction of the conductive glass; the average length of the indium tin oxide nanorods is 440nm; the average diameter is 20nm. The thickness of the graphene is 1.5nm. The square resistance of the conductive glass is 39Ω / sq; the light transmittance in the wavelength range of 400-800nm ​​is 83.5%.

[0043] A method for preparing a conductive glass according to the present embodiment comprises the following steps:

[0044] S1. Preparation of indium tin oxide nanorods: Using Au as a catalyst, indium tin oxide, tin oxide and activated carbon were reacted at high temperature under argon gas flow to prepare indium tin oxide nanorods on a silicon substrate. The detailed preparation process is as follows: 8 parts of indium oxide, 1.6 parts of tin oxide and 0.9 parts of activated carbon were mixed evenly by weight and loaded into an alumina boat. The alumina boat containing the mixture was placed in the center of the first heating zone of a three-zone tube furnace. At the same time, a 5.1 nm Au layer was prepared on the silicon substrate cleaned by sonication by magnetron sputtering. It is then placed in the third heating zone, and argon is used as the carrier gas with a flow rate set to 92 sccm. During the reaction, the temperature of the first heating zone is increased to 880°C at a heating rate of 6.5°C / min and kept warm for 56 minutes. At the same time, the temperature of the third heating zone is heated to 859°C at the same heating rate and a constant temperature reaction is maintained. After 69 minutes of reaction, the furnace is cooled to room temperature, and then the crude indium tin oxide nanorods on the silicon substrate in the alumina boat in the third heating zone are collected, and then ground and screened to obtain the indium tin oxide nanorods.

[0045] S2. Preparation of graphene: Graphene is prepared by a modified Hummers method combined with a chemical reduction method; the detailed preparation process is as follows: by weight, 1.6 parts of natural graphite are added to a stirring bottle, followed by adding 19 parts of 98wt.% concentrated sulfuric acid, stirring for 5 minutes in an ice bath at 1.5°C to form a uniform dispersion system, then slowly adding 3.6 parts of potassium permanganate, maintaining a stirring rate of 290rpm, stirring for 135 minutes at 47°C to form an oxidized graphite intermediate, then transferring the obtained oxidized graphite intermediate to a 97°C glycerol bath, slowly adding 29 parts of deionized water, and maintaining stirring for 13 minutes, then slowly dropping 3.3 parts of 30wt.% hydrogen peroxide solution to terminate the oxidation reaction to obtain an oxidized graphite suspension, and the obtained oxidized graphite suspension is subjected to solid-liquid separation by vacuum filtration through a Buchner funnel, retaining the filter cake, and filtering. The cake was washed three times with 0.2 mol / L hydrochloric acid and deionized water in sequence, with the volume of each washing liquid being 3.9 times the volume of the precipitate. The washed graphite oxide dispersion was centrifuged at a centrifugal rate of 5200 rpm for 16 min, the supernatant was discarded, the precipitate was collected, and finally, the obtained graphene oxide dispersion was dried at 69° C. under vacuum for 31 h to obtain graphene oxide powder. The graphene oxide powder was then redispersed in 65 mL of deionized water, stirred evenly, 6.5 parts of 25 wt.% tetramethylammonium hydroxide were added, and then 1.9 parts of L-ascorbic acid were added dropwise, stirred at 59° C. for 57 min, and the reaction was stopped after the color changed from yellowish brown to black. The obtained reduced graphene oxide was centrifuged at a centrifugal rate of 7200 rpm for 26 min, then washed four times with deionized water, and finally dried in vacuum for 31 h to obtain graphene powder.

[0046] S3. Preparation of composite sol: The initial sol was prepared by reflux reaction of indium chloride and tin chloride in acetylacetone and ethanol system, and the composite sol was prepared by introducing graphene and indium tin oxide nanorods by ultrasonic dispersion method; the detailed preparation process was as follows: 9.2 parts of indium chloride and 15.9 parts of acetylacetone were mixed by weight, the mixed raw materials were placed in a three-necked flask, stirred at a stirring rate of 360 rpm for 39 minutes to obtain a uniform mixed solution, and then the obtained solution was transferred to a reflux device and continued to be stirred at a stirring rate of 460 rpm for 6 9min to obtain a uniform indium chloride complex solution, the complex solution was heated to 86.5°C at a heating rate of 2.9°C / min, and kept warm for 69min. Stirring was continued during the insulation period. After the insulation was completed, 0.7 parts of graphene, 4.5 parts of indium tin oxide nanorods and 0.3 parts of polyvinyl pyrrolidone were added, followed by ultrasonic treatment at 86kHz for 35min, and then 4.2 parts of 0.03mol / L tin chloride ethanol solution were slowly added, and constant temperature stirring was maintained for 69min. After the reaction was completed, the sol was naturally cooled to room temperature to obtain a composite sol.

[0047] S4. Preparation of conductive glass: The composite sol is coated on a soda-lime glass substrate, dried and annealed at high temperature to obtain conductive glass. The detailed preparation process is: the composite sol is coated on a corundum substrate and dried at 365°C to constant weight, and finally annealed at 515°C in a mixed atmosphere of nitrogen and hydrogen, wherein the volume ratio of nitrogen to hydrogen is 95:5 for 78 minutes, and the conductive glass is obtained after cooling to room temperature.

[0048] Example 3

[0049] A conductive glass, the conductive glass is composed of graphene and indium tin oxide; the volume ratio of graphene to indium tin oxide is 3.4:96.6; the graphene presents a three-dimensional interconnected network structure in the conductive glass; the indium tin oxide contains crystalline indium tin oxide nanorods; the indium tin oxide nanorods account for 11.0% of the volume fraction of the conductive glass; the average length of the indium tin oxide nanorods is 680nm; the average diameter is 31nm. The thickness of the graphene is 1.9nm. The square resistance of the conductive glass is 25Ω / sq; the light transmittance in the wavelength range of 400-800nm ​​is 82.1%.

[0050] A method for preparing a conductive glass according to the present embodiment comprises the following steps:

[0051] S1. Preparation of indium tin oxide nanorods: Using Au as a catalyst, indium tin oxide, tin oxide and activated carbon are reacted at high temperature under argon gas flow to prepare indium tin oxide nanorods on a silicon substrate; the detailed preparation process is as follows: 11 parts of indium oxide, 2.2 parts of tin oxide and 1.4 parts of activated carbon are mixed evenly by weight and loaded into an alumina boat, the alumina boat containing the mixture is placed in the center of the first heating zone of a three-temperature zone tube furnace, and a 7.2 nm Au layer is prepared on the silicon substrate cleaned by sonication by magnetron sputtering. It is then placed in the third heating zone, and argon is used as the carrier gas with a flow rate set to 104 sccm. During the reaction, the temperature of the first heating zone is increased to 910°C at a heating rate of 8°C / min and kept warm for 62 minutes. At the same time, the temperature of the third heating zone is heated to 868°C at the same heating rate and a constant temperature reaction is maintained. After 78 minutes of reaction, the furnace is cooled to room temperature, and then the crude indium tin oxide nanorods on the silicon substrate in the alumina boat in the third heating zone are collected, and then ground and screened to obtain the indium tin oxide nanorods.

[0052] S2. Preparation of graphene: Graphene is prepared by a modified Hummers method combined with a chemical reduction method; the detailed preparation process is as follows: by weight, 2.2 parts of natural graphite are added to a stirring bottle, followed by adding 26 parts of 98wt.% concentrated sulfuric acid, stirring for 7 minutes in a 3°C ice bath to form a uniform dispersion system, then slowly adding 4.2 parts of potassium permanganate, maintaining a stirring rate of 380rpm, stirring for 180 minutes at 48°C to form an oxidized graphite intermediate, then transferring the obtained oxidized graphite intermediate to a 98°C glycerol bath, slowly adding 38 parts of deionized water, and maintaining stirring for 16 minutes, then slowly dropping 4.0 parts of 30wt.% hydrogen peroxide solution to terminate the oxidation reaction to obtain an oxidized graphite suspension, and the obtained oxidized graphite suspension is subjected to solid-liquid separation by vacuum filtration through a Buchner funnel, retaining the filter cake, and filtering. The cake was washed three times with 0.3 mol / L hydrochloric acid and deionized water in sequence, and the volume of each washing liquid was 4.8 times the volume of the precipitate. The washed graphite oxide dispersion was centrifuged at a centrifugal rate of 6400 rpm for 22 min, the supernatant was discarded, and the precipitate was collected. Finally, the obtained graphene oxide dispersion was dried at 78 ° C under vacuum for 38 h to obtain graphene oxide powder. Then, the graphene oxide powder was redispersed in 80 mL of deionized water, stirred evenly, 8 parts of 25 wt.% tetramethylammonium hydroxide were added, and then 3.0 parts of L-ascorbic acid were added dropwise, stirred at 68 ° C for 84 min, and the reaction was stopped after the color changed from yellow brown to black. The obtained reduced graphene oxide was centrifuged at a centrifugal rate of 8400 rpm for 32 min, then washed 4 times with deionized water, and finally dried in vacuum for 38 h to obtain graphene powder.

[0053] S3. Preparation of composite sol: an initial sol is prepared by reflux reaction of indium chloride and tin chloride in acetylacetone and ethanol system, and graphene and indium tin oxide nanorods are introduced by ultrasonic dispersion method to prepare composite sol; the detailed preparation process is as follows: 10.4 parts of indium chloride and 19.8 parts of acetylacetone are mixed by weight, the mixed raw materials are placed in a three-necked flask, stirred at a stirring rate of 420 rpm for 48 minutes to obtain a uniform mixed solution, and then the resulting solution is transferred to a reflux device and continued to be stirred at a rate of 520 rpm. The mixture was stirred for 78 minutes to obtain a uniform indium chloride complex solution, and the complex solution was heated to 88°C at a heating rate of 3.8°C / min and kept warm for 78 minutes. Stirring was continued during the insulation period. After the insulation was completed, 0.9 parts of graphene, 6 parts of indium tin oxide nanorods and 0.4 parts of polyvinyl pyrrolidone were added, followed by ultrasonic treatment at 92kHz for 39 minutes, and then 5.4 parts of 0.04 mol / L tin chloride ethanol solution were slowly added, and constant temperature stirring was maintained for 78 minutes. After the reaction was completed, the sol was naturally cooled to room temperature to obtain a composite sol.

[0054] S4. Preparation of conductive glass: The composite sol is coated on a soda-lime glass substrate, dried and annealed at high temperature to obtain conductive glass. The detailed preparation process is: the composite sol is coated on a corundum substrate and dried at 380°C to constant weight, and finally annealed at 530°C in a mixed atmosphere of nitrogen and hydrogen, wherein the volume ratio of nitrogen to hydrogen is 95:5 for 96 minutes, and the conductive glass is obtained after cooling to room temperature.

[0055] Example 4

[0056] A conductive glass, the conductive glass is composed of graphene and indium tin oxide; the volume ratio of graphene to indium tin oxide is 5.0:95.0; the graphene presents a three-dimensional interconnected network structure in the conductive glass; the indium tin oxide contains crystalline indium tin oxide nanorods; the indium tin oxide nanorods account for 15.0% of the volume fraction of the conductive glass; the average length of the indium tin oxide nanorods is 1000nm; the average diameter is 45nm. The thickness of the graphene is 2.5nm. The square resistance of the conductive glass is 20Ω / sq; the light transmittance in the wavelength range of 400 to 800nm ​​is 80%.

[0057] A method for preparing a conductive glass according to the present embodiment comprises the following steps:

[0058] S1. Preparation of indium tin oxide nanorods: Using Au as a catalyst, indium tin oxide, tin oxide and activated carbon are reacted at high temperature under argon gas flow to prepare indium tin oxide nanorods on a silicon substrate; the detailed preparation process is as follows: 15 parts of indium oxide, 3.0 parts of tin oxide and 2.0 parts of activated carbon are mixed evenly by weight and loaded into an alumina boat, the alumina boat containing the mixture is placed in the center of the first heating zone of a three-temperature zone tube furnace, and a 10.0 nm Au layer is prepared on the silicon substrate cleaned by sonication by magnetron sputtering. It is then placed in the third heating zone, and argon is used as the carrier gas with a flow rate set to 120 sccm. During the reaction, the temperature of the first heating zone is increased to 950°C at a heating rate of 10°C / min and kept warm for 70 minutes. At the same time, the temperature of the third heating zone is heated to 880°C at the same heating rate and a constant temperature reaction is maintained. After 90 minutes of reaction, the furnace is cooled to room temperature, and then the crude indium tin oxide nanorods on the silicon substrate in the alumina boat in the third heating zone are collected, and then ground and screened to obtain the indium tin oxide nanorods.

[0059] S2. Preparation of graphene: Graphene is prepared by a modified Hummers method combined with a chemical reduction method; the detailed preparation process is as follows: by weight, 3.0 parts of natural graphite are added to a stirring bottle, followed by 35 parts of 98wt.% concentrated sulfuric acid, stirred for 10 minutes in an ice bath at 5°C to form a uniform dispersion system, then 5.0 parts of potassium permanganate are slowly added, the stirring rate is maintained at 500rpm, and stirred for 240 minutes at 50°C to form an oxidized graphite intermediate, then the obtained oxidized graphite intermediate is transferred to a 100°C glycerol bath, 50 parts of deionized water are slowly added, and stirring is maintained for 20 minutes, then 5.0 parts of 30wt.% hydrogen peroxide solution are slowly added dropwise to terminate the oxidation reaction to obtain an oxidized graphite suspension, the obtained oxidized graphite suspension is subjected to solid-liquid separation by vacuum filtration through a Buchner funnel, the filter cake is retained, and the filter is filtered. The cake was washed three times with 0.5 mol / L hydrochloric acid and deionized water in sequence, and the volume of each washing liquid was 6 times the volume of the precipitate. The washed graphite oxide dispersion was centrifuged at a centrifugal rate of 8000 rpm for 30 min, the supernatant was discarded, and the precipitate was collected. Finally, the obtained graphene oxide dispersion was dried at 90 ° C under vacuum for 48 h to obtain graphene oxide powder. Then, the graphene oxide powder was redispersed in 100 mL of deionized water, stirred evenly, 10 parts of 25 wt.% tetramethylammonium hydroxide were added, and then 4.5 parts of L-ascorbic acid were added dropwise, stirred at 80 ° C for 120 min, and the reaction was stopped after the color changed from yellow brown to black. The obtained reduced graphene oxide was centrifuged at a centrifugal rate of 10000 rpm for 40 min, then washed 5 times with deionized water, and finally dried in vacuum for 48 h to obtain graphene powder.

[0060] S3. Preparation of composite sol: an initial sol is prepared by reflux reaction of indium chloride and tin chloride in acetylacetone and ethanol system, and graphene and indium tin oxide nanorods are introduced by ultrasonic dispersion method to prepare composite sol; the detailed preparation process is as follows: 12.0 parts of indium chloride and 25.0 parts of acetylacetone are mixed by weight, the mixed raw materials are placed in a three-necked flask, stirred at a stirring rate of 500 rpm, stirred for 60 minutes, and a uniform mixed solution is obtained, and then the resulting solution is transferred to a reflux device, and the stirring rate is continued at 600 rpm. The mixture was stirred for 90 minutes to obtain a uniform indium chloride complex solution, and the complex solution was heated to 90°C at a heating rate of 5°C / min and kept warm for 90 minutes. Stirring was continued during the insulation period. After the insulation was completed, 1.2 parts of graphene, 8.0 indium tin oxide nanorods and 0.5 parts of polyvinyl pyrrolidone were added, followed by ultrasonic treatment at 100kHz for 45 minutes, and then 7.0 parts of 0.06 mol / L tin chloride ethanol solution were slowly added, and constant temperature stirring was maintained for 90 minutes. After the reaction was completed, the sol was naturally cooled to room temperature to obtain a composite sol.

[0061] S4. Preparation of conductive glass: The composite sol is coated on a soda-lime glass substrate, dried and annealed at high temperature to obtain conductive glass. The detailed preparation process is: the composite sol is coated on a corundum substrate and dried at 400°C to constant weight, and finally annealed at 550°C in a mixed atmosphere of nitrogen and hydrogen, wherein the volume ratio of nitrogen to hydrogen is 95:5, for 120 minutes, and the conductive glass is obtained after cooling to room temperature.

[0062] Comparative Example 1

[0063] It is basically the same as Example 1, except that graphene is not introduced, and only indium tin oxide nanorods are used as conductive filling material.

[0064] Comparative Example 2

[0065] It is basically the same as Example 1, except that the graphene thickness is adjusted to 4.0 nm and other parameters are kept unchanged.

[0066] Comparative Example 3

[0067] The method is basically the same as Example 1, except that the length of the indium tin oxide nanorods is adjusted to 1200-1500 nm.

[0068] Comparative Example 4

[0069] The method is substantially the same as Example 1, except that the volume fraction of the indium tin oxide nanorods is adjusted to 2.0%.

[0070] Comparative Example 5

[0071] It is basically the same as Example 1, except that indium tin oxide nanorods are not introduced, and only graphene is used as the conductive filling material.

[0072] Comparative Example 6

[0073] The method is substantially the same as Example 1, except that the volume fraction of the indium tin oxide nanorods is increased by 20%.

[0074] Comparative Example 7

[0075] The method is basically the same as Example 1, except that polyvinyl pyrrolidone is not added and other parameters remain unchanged.

[0076] Comparative Example 8

[0077] The method is basically the same as Example 1, except that the annealing temperature is lowered to 450°C.

[0078] Performance Testing:

[0079] The sheet resistance of conductive glass was measured using the Four-Point Probe Method. In a constant temperature and humidity environment, a Keithley 2400 digital source meter was used to apply a constant current to the sample, and the corresponding voltage was recorded to calculate the sheet resistance. Five different areas of each sample were tested and the average value was taken.

[0080] Transmittance test: Use a UV-Vis spectrophotometer to measure the light transmittance of conductive glass in the wavelength range of 400-800nm. Place the sample on an optical stand, record the transmittance curves at different wavelengths, and calculate the average transmittance. Compare conductive glasses prepared under different components and process conditions, and analyze the impact of different characteristics on transparency.

[0081] Thermal stability test: Place the sample in a high-temperature furnace and perform constant temperature annealing at 100-500°C. Test the sheet resistance and transmittance every 50°C to evaluate its high-temperature stability. By comparing the performance changes at different annealing temperatures, analyze the material's ability to maintain a conductive network in a high-temperature environment to ensure its reliability in high-temperature applications such as photovoltaic devices.

[0082] Mechanical bending test: Conductive glass is subjected to 0 to 1000 cycles of bending test using a bending test device. The bending radius is set to 5 mm, and the change in square resistance is measured every 100 times to evaluate the flexibility stability. After the test, the film is observed to see if cracks appear or the conductivity decreases, in order to verify the application potential of the material in flexible electronic devices.

[0083] The properties of the conductive glasses of Examples 1 to 4 and Comparative Examples 1 to 8 are summarized in Table 1.

[0084] Table 1 Performance of conductive glass of Examples 1 to 4 and Comparative Examples 1 to 8

[0085]

[0086] As can be seen from Table 1, after removing graphene, the conductive path is discontinuous, resulting in a significant increase in the sheet resistance, while the thermal stability and mechanical bending performance deteriorate; although increasing the graphene thickness can reduce the sheet resistance, the excessively thick graphene layer enhances light absorption, causing a significant decrease in transmittance; increasing the length of the indium tin oxide nanorods will slightly improve the conductive performance, but the film uniformity deteriorates, resulting in a decrease in transmittance; reducing the indium tin oxide nanorod content will make the conductive network discontinuous, the sheet resistance increases, but the transmittance does not change much; after removing the indium tin oxide nanorods, the sheet resistance increases significantly, the transmittance decreases, and the thermal stability is poor; increasing the indium tin oxide nanorod content can reduce the sheet resistance, but due to enhanced light scattering, the transmittance decreases; lack of polyvinyl pyrrolidone will cause the film uniformity to deteriorate, the sheet resistance increases, and the transmittance decreases; lowering the annealing temperature increases the sheet resistance, and the thermal stability decreases significantly.

[0087] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.

Claims

1. A conductive glass, characterized in that: The conductive glass is composed of graphene and indium tin oxide; The volume ratio of graphene to indium tin oxide is (1.0-5.0): (99.0-95.0); The graphene presents a three-dimensional interconnected network structure in the conductive glass; The indium tin oxide contains crystalline indium tin oxide nanorods; The indium tin oxide nanorods account for 5.0% to 15.0% of the volume fraction of the conductive glass; The average length of the indium tin oxide nanorods is 200-1000nm; the average diameter is 10-45nm.

2. A conductive glass as claimed in claim 1, characterized in that: The thickness of the graphene is 1.0-2.5 nm.

3. The conductive glass according to claim 1, characterized in that: The conductive glass block resistance is 20-50Ω / sq; the light transmittance in the wavelength range of 400-800nm ​​is 80-85%.

4. A method for preparing a conductive glass according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Preparation of indium tin oxide nanorods: Using Au as a catalyst, indium tin oxide, tin oxide and activated carbon are reacted at high temperature under argon gas flow to prepare indium tin oxide nanorods on a silicon substrate; S2. Preparation of graphene: Graphene is prepared by a modified Hummers method combined with a chemical reduction method; S3. Preparation of composite sol: preparing an initial sol by reflux reaction of indium chloride and tin chloride in acetylacetone and ethanol system, and introducing graphene and indium tin oxide nanorods to prepare a composite sol by ultrasonic dispersion method; S4. Preparation of conductive glass: The composite sol is coated on a soda-lime glass substrate, dried and annealed at a high temperature to obtain the conductive glass.

5. The method for preparing a conductive glass according to claim 4, characterized in that: The detailed preparation process of step S1 is as follows: 5 to 15 parts of indium oxide, 1.0 to 3.0 parts of tin oxide and 0.5 to 2.0 parts of activated carbon are mixed uniformly by weight and loaded into an alumina boat, the alumina boat containing the mixture is placed in the center of the first heating zone of a three-zone tube furnace, and a 3.0 to 10.0 nm Au layer is prepared on the silicon substrate cleaned by sonication by magnetron sputtering, and then placed in the third heating zone, and then argon is used as a carrier gas with a flow rate set to 80 to 1 20sccm, during the reaction process, the temperature of the first heating zone is increased to 850-950°C at a heating rate of 5-10°C / min, and kept warm for 50-70min, and the temperature of the third heating zone is heated to 850-880°C at the same heating rate, and the reaction is kept at a constant temperature. After the reaction is carried out for 60-90min, the furnace is cooled to room temperature, and then the crude indium tin oxide nanorods on the silicon substrate in the alumina boat in the third heating zone are collected, and then the indium tin oxide nanorods are obtained after grinding and screening.

6. The method for preparing a conductive glass according to claim 4, characterized in that: The detailed preparation process of step S2 is as follows: by weight, 1.0 to 3.0 parts of natural graphite are added to a stirring bottle, followed by adding 12 to 35 parts of 98 wt.% concentrated sulfuric acid, stirring for 3 to 10 minutes in an ice bath at 0 to 5°C to form a uniform dispersion system, then slowly adding 3.0 to 5.0 parts of potassium permanganate, maintaining a stirring rate of 200 to 500 rpm, stirring for 90 to 240 minutes at 45 to 50°C to form an oxidized graphite intermediate, then transferring the obtained oxidized graphite intermediate to a glycerol bath at 95 to 100°C, slowly adding 20 to 50 parts of deionized water, and maintaining stirring for 10 to 20 minutes, then slowly dropping 2.5 to 5.0 parts of 30 wt.% hydrogen peroxide solution to terminate the oxidation reaction to obtain an oxidized graphite suspension, and performing solid-liquid separation on the obtained oxidized graphite suspension by vacuum filtration through a Buchner funnel, retaining the filter cake, and sequentially rinsing the filter cake with 0.1 to 0.5 mol / L hydrochloric acid and deionized water. The obtained graphene oxide dispersion is centrifuged at a centrifugal rate of 4000-8000rpm for 10-30min, the supernatant is discarded, and the precipitate is collected. Finally, the obtained graphene oxide dispersion system is dried under vacuum drying at 60-90°C for 24-48h to obtain graphene oxide powder. Then, the graphene oxide powder is redispersed in 50-100mL deionized water, stirred evenly, 5-10 parts of 25wt.% tetramethylammonium hydroxide are added, and then 0.8-4.5 parts of L-ascorbic acid are added dropwise, stirred at 50-80°C for 30-120min, and the reaction is stopped after the color changes from yellow-brown to black. The obtained reduced graphene oxide is centrifuged at a centrifugal rate of 6000-10000rpm for 20-40min, then washed with deionized water for 3-5 times, and finally dried in vacuum for 24-48h to obtain graphene powder.

7. The method for preparing a conductive glass according to claim 4, characterized in that: The detailed preparation process of step S3 is as follows: 8.0-12.0 parts of indium chloride and 12.0-25.0 parts of acetylacetone are mixed by weight, the mixed raw materials are placed in a three-necked flask, stirred at a stirring rate of 300-500 rpm for 30-60 minutes to obtain a uniform mixed solution, then the obtained solution is transferred to a reflux device, and the stirring rate is continued at 400-600 rpm for 60-90 minutes to obtain a uniform indium chloride complex solution, and the complex solution is heated at a heating rate of 2-5°C / min. The method comprises heating the mixture to 85-90° C. and keeping the mixture warm for 60-90 minutes, stirring the mixture continuously during the keeping period, and then adding 0.5-1.2 parts of graphene, 3.0-8.0 parts of indium tin oxide nanorods and 0.2-0.5 parts of polyvinyl pyrrolidone after the keeping period, and then ultrasonically treating the mixture at 80-100 kHz for 30-45 minutes, and then slowly adding 3.0-7.0 parts of 0.02-0.06 mol / L tin chloride ethanol solution, and keeping the stirring at a constant temperature for 60-90 minutes. After the reaction is completed, the sol is naturally cooled to room temperature to obtain a composite sol.

8. A method for preparing a conductive glass as claimed in claim 4, wherein the detailed preparation process of step S4 is: coating the composite sol on a corundum substrate and drying it at 350-400° C. to constant weight, and finally annealing at 500-550° C. in a mixed atmosphere of nitrogen and hydrogen, wherein the volume ratio of nitrogen to hydrogen is 95:5, for 60-120 min, and cooling to room temperature to obtain the conductive glass.

Citation Information

Patent Citations

  • Preparation method of ITO (Indium Tin Oxide) conductive glass and ITO conductive glass

    CN117865505A

Cited By

  • Transparent film with electromagnetic field shielding performance and preparation method thereof

    CN120881964A